2018
DOI: 10.1111/clr.13270
|View full text |Cite|
|
Sign up to set email alerts
|

Drugs and diseases: Summary and consensus statements of group 1. The 5thEAO Consensus Conference 2018

Abstract: Objectives:The task of this working group was to update the knowledge about the use of drugs and biologicals affecting healing of soft tissue and bone during implant treatment or procedures associated with it. Moreover, the impact of titanium particles and biocorrosion on complications and implant survival has been analysed. Materials and Methods:The literature in the areas of interest (platelet concentrates, antiresorptive drugs as well as implant-host interaction) was screened using systematic reviews for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…The European Association for Osseointegration (EAO) Consensus Conference 2018 published a final statement [ 36 ], which includes an extensive discussion of the effects of titanium particles and biocorrosion on implant complications and subsequent survival rates. According to the statement, a number of in vitro studies have reported that the acidity of the oral environment caused by bacterial biofilm and/or inflammatory processes can provoke titanium particle release in a process known as “biocorrosion.” The resulting titanium debris upsets the balance between bone formation and resorption in two ways: through direct osteoclast and osteoblast activation and through the stimulation of inflammatory cytokine secretion from macrophages and lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
“…The European Association for Osseointegration (EAO) Consensus Conference 2018 published a final statement [ 36 ], which includes an extensive discussion of the effects of titanium particles and biocorrosion on implant complications and subsequent survival rates. According to the statement, a number of in vitro studies have reported that the acidity of the oral environment caused by bacterial biofilm and/or inflammatory processes can provoke titanium particle release in a process known as “biocorrosion.” The resulting titanium debris upsets the balance between bone formation and resorption in two ways: through direct osteoclast and osteoblast activation and through the stimulation of inflammatory cytokine secretion from macrophages and lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Further, except from the above‐mentioned single case of tissue discoloration, no clinical study included in this review mentioned any other adverse event related to titanium particle deposition, despite the variable type of burs used and most likely the variable amount of deposition. In this context, a very recent consensus report concluded that on the basis of the available evidence, although the possibility cannot unequivocally be excluded, it is not likely that titanium particles elicit adverse biological reactions in the peri‐implant tissues (Schliephake et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For its gel form, thrombin and/or calcium chloride is added to induce fibrin polymerization creating a low-density fibrin gel preparation. For platelet-rich fibrin (PRF), blood is collected without any anticoagulant, and it is immediately centrifugated, during which the natural coagulation process occurs [36,37]. The use of autologous platelet concentrates in the different fields of dentistry started in the 1980-1990s.…”
Section: Rationalementioning
confidence: 99%